Strategi Pengelolaan Dan Perencanaan Keuangan Desa Tahun 2023 (Studi Pada Kantor Desa Sekarwangi Kecamatan Cibadak Kabupaten Sukabumi) - Rachmat Pramukty; Arfian Arfian; Gatot Efrianto; Bambang Rudiansyah; Yusef Wandy; Heru Irianto; Vera Rimbawani Sushanty; Satrio Waliyudin Azhar; Belva Yulivio Estiawan; Muhammad Kamil Hafidzi; Manarul Hidayat; Salsabila Putri Azzahra; Ananda Intan Fadhilah Yahya; Akmal Hidayatullah; Al Fachri Nurfath; Denisa Ramadhanty; Lala Intan Nurcahyani; Ade Armeita; Birkham Pahmi Safaat; Anyeu Riandini; Fauzi Maulana Yusuf; Yudi Nurahim; Annisa Septi Rahayu Salsabila; Fajar Wira Warhana; Firiyal Luthfi Syihab; Raafi Catur Wahyudianto; Daffa Satrio Wibowo; Alif Fito Dermawan; Aulia Rohman Malau; Fifi Nur Alfianti; Vella Dwi Anggraini; Betris Kristin Sosor Ambar Wati Sitorus (Jurnal Kajian Ilmiah, 2023)
The level of responsibility in planning and managing village finances. The method used in this research is qualitative, with data collection carried out through interviews, observation and document analysis. The research results show that the Sekarwangi village office has implemented special actions to increase the accountability of village financial planning, such as implementing a village financial information system and attracting active community participation in the planning process. However, this study also identified a number of obstacles faced by village level offices in achieving harmonious accountability, such as limited human resources and limited technology. Therefore, this research provides suggestions for increasing the accountability of village-level financial planning, including human resource training and improving technological infrastructure. This study provides valuable insight into the efforts of the Sekarwangi Village Office in realizing harmonization of accountability in village financial planning, which can be a basis for further improvements in village financial management, not only in Sekarwangi Village but also in all villages.